Foreign Ownership of Firms and Corruption in Africa - Abotsi, Anselm Komla (International Journal of Economics and Financial Issues, 2015)
The study finds the impact of the percentage of total annual sales of a firm paid as informal payments to public officials (bribes) on foreign ownership of firms in Africa while controlling for other variables outside the country of origin of investment. The study used secondary data from the World Business Environment Survey (WBES) conducted by the World Bank. In all 3,290 firms made up of the manufacturing, services and retail sectors are included in the analysis. The Tobit and probit estimation techniques were used. The results indicate that the percentage of total annual sales of the firm paid as informal payments to the public officials has a negative and highly significant impact on foreign ownership of firms in Africa. African leaders should therefore institute policies to control corruption in order to boost foreign investors’ confidence in their economies. Keywords: foreign ownership of firm; informal payments; corruption; institutions; foreign investors JEL Classifications: F21; F23; F32